PELATIHAN PUBLIC SPEAKING DAN TATA RIAS SANGGUL SEBAGAI UPAYA PENINGKATAN SOFT SKILL MASYARAKAT PADA KEGIATAN BAKTI SOSIAL DI DESA SINGAPADU KALER - Putu Dessy Fridayanthi; Ida Ayu Agung Ekasiadi; Gusti Ayu Made Puspawati (LP3M Universitas PGRI Mahadewa Indonesia, 2026)
This community service activity aims to improve the community's soft skills through public speaking training on polite language on social media and hair buns for temples, as part of the Community Service Program of the University of PGRI Mahadewa Indonesia (UPMI) in Singapadu Kaler Village. The problems faced by the partners included limited public speaking skills, a poor understanding of language etiquette on social media, and a lack of confident communication skills in public. Furthermore, the community lacked a basic understanding of hair bun techniques for temples that align with Balinese cultural aesthetics and lacked practical skills for traditional and religious activities. From a management perspective, there was a lack of ongoing training, support for polite communication, and structured and sustainable hair bun training. The implementation methods included outreach, training, hands-on practice, the application of learning technology, mentoring, and evaluation. The results showed an improvement in the community's communication skills, particularly in public speaking and the use of polite language on social media. Furthermore, participants' hair bun skills also significantly improved through hands-on practice and instructor guidance. This activity has had a positive impact on increasing self-confidence, creativity, and preserving local Balinese culture.